Lipid Profile in Geriatric Patients with Diabetic Nephropathy: A Case-Control Study - Dr Keshavamurthy HR; Dr. Shivakumar; Dr Vinodkumar; Dr Prashantkumar (International Journal of Pharma and Bio Sciences, 2023)
Diabetic nephropathy is one of the common causes of end-stage kidney disease (ESKD). It is a major microvascular complication that occurs among patients with diabetes. Dyslipidaemia is a modifiable cardiovascular risk factor. Hence early intervention can delay or prevent the progression of the disease. Till now, studies were done on lipid profiles in diabetic patients or nephropathy patients, or obese hypertensive patients. The study’s novelty is that we are measuring the lipid profile in diabetic nephropathy patients. The current study aims to assess lipid profiles among diabetic nephropathy patients. The objectives of the study are to compare lipid profiles among diabetic nephropathy patients with diabetic nonnephropathy patients and to identify risk factors associated with abnormal lipid profiles in diabetic nephropathy patients. This study was carried out among 50 samples of diabetic nephropathy patients(cases) and 50 samples of diabetic patients without nephropathy (controls).The study samples were taken from patients who attended the outpatient unit of the General Medicine department at a tertiary care center named Sri Siddhartha Medical College, Tumkur, Karnataka, India. Fasting serum total cholesterol (TC), triglycerides (TGs), high-density lipoprotein cholesterol (HDL-C), and lowdensity lipoprotein-cholesterol (LDL-C) were measured. Results showed that most of the patients were males. Most of the patients were aged 61 to 70 years. TC, LDL-C, and TGs were significantly more among cases than controls. HDL-C was significantly lower among cases compared to controls in the current study. We conclude that diabetes, being a part of metabolic syndrome, may not cause abnormal lipid profiles. Still, the presence of nephropathy or renal damage along with diabetes increases the risk of hyperlipidemia, which keeps the patients at high risk of cardiovascular disorders.